1988
DOI: 10.1099/0022-1317-69-1-23
|View full text |Cite
|
Sign up to set email alerts
|

Gene Mapping and Positive Identification of the Non-structural Proteins NS2A, NS2B, NS3, NS4B and NS5 of the Flavivirus Kunjin and Their Cleavage Sites

Abstract: SUMMARYPartial N-terminal amino acid analyses of five radiolabelled non-structural (ns) proteins specified by Kunjin (KUN) virus provided positive identification of NS3, NS5 and three previously hypothetical ns proteins of flaviviruses, ns2a, ns2b and ns4b. Their correct gene order was obtained from their deduced amino acid sequences. Thus the gene order for KUN virus relative to that proposed for yellow fever (YF) virus was as follows: KUN 5'...GP44-P19.P10.P71.(?)-P21-P98-3', YF 5'...NSl.ns2a.ns2b.NS3.ns4a-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 44 publications
3
82
0
Order By: Relevance
“…Experiments on a number of different flaviviruses showed that the cleavages between the C\prM, prM\E, E\NS1, NS1\NS2A and NS4A-B proteins are mediated by host-cell proteinases (Biedrzycka et al, 1987 ;Nowak et al, 1989 ;Ruiz-Linares et al, 1989 ;Speight et al, 1988 ;Markoff, 1989 ;Wright et al, 1989 ;Lin et al, 1993 ;Lobigs, 1993 ;Yamshchikov & Compans, 1994Falgout & Markoff, 1995). Sites of other processing events (identified by N-terminal sequencing of virus proteins) occurred at motifs commonly consisting of dibasic amino acid pairs at P1 and P2 followed by a small, non-branched amino acid at P1h (Rice et al, 1986 ;Biedrzycka et al, 1987 ;Speight et al, 1988 ;Chambers et al, 1989). These sites proved to be conserved amongst the flavivirus sequences then becoming available (Rice et al, 1985 ;Castle et al, 1986 ;Sumiyoshi et al, 1987 ;Coia et al, 1988 ;Hahn et al, 1988 ;Pletnev et al, 1990).…”
Section: (Asterisks)mentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments on a number of different flaviviruses showed that the cleavages between the C\prM, prM\E, E\NS1, NS1\NS2A and NS4A-B proteins are mediated by host-cell proteinases (Biedrzycka et al, 1987 ;Nowak et al, 1989 ;Ruiz-Linares et al, 1989 ;Speight et al, 1988 ;Markoff, 1989 ;Wright et al, 1989 ;Lin et al, 1993 ;Lobigs, 1993 ;Yamshchikov & Compans, 1994Falgout & Markoff, 1995). Sites of other processing events (identified by N-terminal sequencing of virus proteins) occurred at motifs commonly consisting of dibasic amino acid pairs at P1 and P2 followed by a small, non-branched amino acid at P1h (Rice et al, 1986 ;Biedrzycka et al, 1987 ;Speight et al, 1988 ;Chambers et al, 1989). These sites proved to be conserved amongst the flavivirus sequences then becoming available (Rice et al, 1985 ;Castle et al, 1986 ;Sumiyoshi et al, 1987 ;Coia et al, 1988 ;Hahn et al, 1988 ;Pletnev et al, 1990).…”
Section: (Asterisks)mentioning
confidence: 99%
“…Sites of other processing events (identified by N-terminal sequencing of virus proteins) occurred at motifs commonly consisting of dibasic amino acid pairs at P1 and P2 followed by a small, non-branched amino acid at P1h (Rice et al, 1986 ;Biedrzycka et al, 1987 ;Speight et al, 1988 ;Chambers et al, 1989). These sites proved to be conserved amongst the flavivirus sequences then becoming available (Rice et al, 1985 ;Castle et al, 1986 ;Sumiyoshi et al, 1987 ;Coia et al, 1988 ;Hahn et al, 1988 ;Pletnev et al, 1990). Recently, it has been shown that a cleavage within the final helicase motif in the Cterminal region of dengue virus type 2 NS3 (Fig.…”
Section: (Asterisks)mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the amino termini of proteins NS2B, NS3, NS4A and NS5 are preceded by a protease consensus sequence which contains multiple basic amino acid residues (Rice et al, 1985(Rice et al, , 1986Biedrzycka et al, 1987;Speight et al, 1988;Chambers et al, 1989;Wright et al, 1989;Wengler et al, 1990) and it has been proposed that a cytosolic virus-encoded protease which cleaves after double basic residues is responsible for the corresponding proteolytic cleavages (Rice et al, 1985;Speight et al, 1988). Recently, a computer search of conserved amino acid residues has led to the suggestion that the amino-terminal segment of the NS3 protein represents a serine protease (Bazan & Fletterick, 1989;Gorbalenya et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…All virus-encoded proteins identified thus far are derived from the encoded polyprotein. Analysis of terminal sequences of virus-encoded proteins has shown that the viral structural and non-structural (NS) proteins are organized on the polyprotein in the order, core protein-envelope protein (pre-M)-envelope protein (E) -NS1 -NS2A -NS2B -NS3 -NS4A -NS4B -NS5 (Rice et al, 1985(Rice et al, , 1986Castle et al, 1986;Speight et al, 1988;Chambers et al, 1989;Speight & Westaway, 1989b;Wright et al, 1989;Wengler et al, 1990).…”
Section: Introductionmentioning
confidence: 99%